Sedative and Hypnotic Activities of the Methanolic and Aqueous Extracts of Lavandula officinalis from Morocco - Rachad Alnamer; Katim Alaoui; El Houcine Bouidida; Abdelaziz Benjouad; Yahia Cherrah (Advances in Pharmacological Sciences)
We evaluate the sedative and hypnotic activities of the methanolic and aqueous extract of Lavandula officinalis L. on central nervous system (CNS). In this study, the effect of the methanolic and aqueous extracts of this plant was investigated in a battery of behavioural models in mice. Stems and flowers of Lavandula officinalis L. have several therapeutic applications in folk medicine in curing or managing a wide range of diseases, including insomnia. The methanolic extract produced significant sedative effect at the doses of 200, 400, and 600 mg/kg (by oral route), compared to reference substance diazepam (DZP), and an hypnotic effect at the doses of 800 and 1000 mg/kg while the treatment of mice with the aqueous extract at the doses of 200 and 400 mg/kg via oral pathway significantly reduced in both the reestablishment time and number of head dips during the traction and hole-board tests. In conclusion, these results suggest that the methanolic and aqueous extracts of Lavandula officinalis possess potent sedative and hypnotic activities, which supported its therapeutic use for insomnia.